Highly discriminant rate of Dianhong black tea grades based on fluorescent probes combined with chemometric methods. (15th November 2019) - Zhu, Jing; Zhu, Fengyuan; Li, Luqing; Cheng, Linlin; Zhang, Liang; Sun, Yue; Wan, Xiaochun; Zhang, Zhengzhu
Highlights: We firstly used CDs to identify eight grades of Dianhong black tea. We firstly increased recognition rate by adding cobalt ions. All materials we used are laboratory-synthesized, and operation is convenient. Abstract: We established a novel Dianhong black tea grades discriminant analytic technique based on a fluorescence image along with carbon quantum dots (CDs) as fluorescent probes. Different grades of Dianhong black tea contain different various amounts of tea polyphenols. Tea polyphenols can quench the fluorescent intensity of CDs, resulting in different fluorescent peaks; Dianhong black tea grades can then be discriminated through the use of principal component analysis and Bayesian analysis. Compared with the additional data processing required in other methods, the advantage of our method is that the fluorescence curve can be used directly, and it achieves satisfactory results. We firstly used CDs combined with chemometrics to identify eight grades of Dianhong black tea, and we also provide a new method that improves the identification rate using nanotechnology to avoid performing complex data processing.